2016
DOI: 10.1007/s10694-015-0540-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study of the Temperatures Field Around a Chimney Roof Penetration

Abstract: The number of roof fires due to the passage of chimneys is high. Since the experimental procedure necessary to identify all the variables affecting the temperature reached by roof in the vicinity of a chimney would be expensive, a 2D numerical model for the estimation of the temperatures in the roof has been designed. The model has been validated by means of experimental tests in which a certified chimney has been installed in three roofs and spaced from flammable materials as prescribed by the manufacturer. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…Data presented in this paper support for previous works [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] on heat transfer at chimney-roof penetration. The data ( Fig.…”
Section: Datasupporting
confidence: 88%
See 2 more Smart Citations
“…Data presented in this paper support for previous works [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] on heat transfer at chimney-roof penetration. The data ( Fig.…”
Section: Datasupporting
confidence: 88%
“…In the experimental campaign extensively described in [1] , [2] , [3] , [4] , [5] , a chimney of 200 mm in diameter was installed in a corner test structure ( C ) and in an axi-simmetric test structure ( A ) respectively. The test structures described in [1] , [4] are both made of an interchangeable roof. The three roofs ( R1, R2, R3 ) installed in the experimental tests are described in [1] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some studies have considered the optimization of the building envelope construction type and the selection of the insulation level for walls, roofs, floors [69,70] and/or chimney-roof penetrations [71][72][73][74]. Some of these researchers also discussed insulation thickness [75][76][77][78][79].…”
Section: Introductionmentioning
confidence: 99%
“…These include, for example, the fact that the actual on-site flue gas temperatures are higher than assumed in chimney design [4,5], faulty installations, use contrary to operating instructions [6] and the smouldering combustion of mineral wool insulation [6][7][8]. Previous research by Neri et al [9][10][11] and Leppa¨nen et al [4,5,12] have also shown that the standard test set-up and conditions are often different from the actual site installations and may not always lead to a safe solution. All the above issues can increase the temperatures in the roof construction.…”
Section: Introductionmentioning
confidence: 99%